Analisis Nilai Pendidikan dalam Rokat Tase’ oleh Masyarakat Muslim Kepulauan Giligenting dan Talango Sumenep Madura - Firdausi (Fakultas Agama Islam Universitas Billfath, 2024)
Religion is a determinant for its adherents, while noble values rooted in a tradition certainly have spiritual-mystical, socio-religious energy believed to strengthen the love between people and bring them closer to God. Giligenting and Talango islands have a tradition of picking the sea with values, norms, ethics, customs, and customary laws highly upheld by the community. Every year, residents working as fishermen organize and interpret it as local wisdom because this tradition directs cultural development. This social-based qualitative research used an ethnographic approach to reveal, explore, and develop data from the research objective, the forms of educational practices, and values in this tradition. Researchers used structured interview techniques, participant observation, and documentation to assist and complete the data. The results show that the two traditions have differences. The difference is that Giligenting no longer removes offerings and replaces them with religious activities. This annual tradition is held using cash from savings and loan members. Meanwhile, in Talango, they are still releasing offerings, holding people's entertainment, and collaborating with the village government. This tradition stands as an expression of gratitude for God's abundance of good fortune. The educational value that can be learned from this tradition is teaching future generations not to be greedy for nature, protecting marine ecosystems, and minimizing conflicts between people. This tradition is successfully held every year with the spirit of cooperation. It is just that in Talango, it is no longer held because residents have changed professions as grocery store traders in Jakarta.